Implementasi Media Infokus pada Pembelajaran Tematik di MIN 16 Aceh Barat - Fandayani, Reti; Jamin, Hanifuddin; Abidah, Abidah (Mitra PGMI: Jurnal Kependidikan MI, 2022)
Media is needed in teaching so that students more easily understand the subject matter being taught. Learning media also includes a part of learning that affects teaching and learning interactions in the classroom. This study aims to determine the implementation of infocus media theme 5 on students of MIN 16 West Aceh and to determine student learning outcomes of MIN 16 West Aceh theme 5 using infocus media. This research is a classroom action research (CAR). Data collection was carried out directly by practicing learning using infocus media in two research cycles, namely cycle 1 and cycle 2. This can be seen from the increase in student learning outcomes, namely in the initial conditions the percentage of student learning completeness is 39.10% increasing to 58.33% after the implementation of cycle 1 and increasing to 79.41% after the implementation of learning cycle 2.